Redescription, molecular features, and neotype deposition of Rhipicephalus pusillus Gil Collado and Ixodes ventalloi Gil Collado (Acari, Ixodidae) - Estrada Peña, Agustin (2018)
Two species of ticks, Rhipicephalus pusillus Gil-Collado and Ixodes ventalloi Gil-Collado are redescribed, their molecular features (16S rDNA) compared with near species, and neotypes named and deposited. The male of R. pusillus is charac-terized by a smooth dorsal surface, with relatively short marginal grooves, not reaching the eyes and reaching the first festoon, longer than wide adanal plates, internally concave and widely rounded posteriorly, without internal spurs, acces-sory adanal plates not projecting over the cuticle, and a narrow, long and straight process on the spiracular plate. The fe-male has very small porose areas, separated by 2.5-3 diameters, and a large triangular spur on the ventro-internal side of the palpal article 1. The nymph has lateral processes curved anteriorly in the ventral aspect of the basis capituli, long au-riculae, and internal spurs on the four coxae. The larva of R. pusillus is separated by the presence of spurs on the ventral surface of palpal segment I, together with the rounded apices of the palpi. Features of 16S rDNA cluster this species near the R. sanguineus s.l. complex of species. The distinctive feature of the female of I. ventalloi is the long and curved au-riculae, which are absent in every other species of Ixodes reported in the Western Palaearctic. The male is characterized by relatively long conscutal setae and deep and well defined cervical fields. The nymph is unique by having slightly ap-parent lateral carinae and small cornua, very abundant and long alloscutal setae, about six times longer than those on the scutum and internal spur of coxa I reaching coxa II. The larva of I. ventalloi has Md1-Md3 setae of the same size as the rest of the conscutal setae, which are only slightly longer than the scutal setae, cornua present, and anal groove clearly divergent. In addition to the unique combination of morphological features, the molecular 16rDNA sequence clearly sep-arates I. ventalloi from other species of the I. ricinus group. We named and deposited in an internationally accessible col-lection the neotypes of both species, since the holotypes were lost.